PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA INDONESIA - Yolanda, Nina (Faculty of Law, University of Palembang, 2020)
The problem of Indonesian Workers (TKI) already exists from the management of a number of labor distribution companies. The factor of the low education of prospective Indonesian Workers is also a problem which results in them facing the risk of being easily cheated by others. In addition the problem occurs because of the lack of understanding of the rules and requirements for working abroad, as well as the falsification of labor documents. Whereas the basic rights inherent in the individual including Indonesian workers are protected in the eyes of the law, so that various problems regarding the torture of Indonesian migrant workers abroad, basically contradict what is stated in the General Statement on Human Rights. The Government has issued legislation to guarantee the protection of Indonesian Workers as migrant workers as stipulated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. The Law on the Protection of Indonesian Migrant Workers also provides legal, social and economic protection.